Dynamics of brain activity underlying working memory for music in a naturalistic condition - Burunat Pérez, Iballa (2012)
Working memory (WM) is at the core of any cognitive function as it is necessary for the integration of information over time. Despite WM’s critical role in high-level cognitive functions, its implementation in the neural tissue is poorly understood. Preliminary studies on auditory WM show differences between linguistic and musical memory, leading to the speculation of specific neural networks encoding memory for music. Moreover, in neuroscience WM has not been studied in naturalistic listening conditions but rather in artificial settings (e.g., n-back and Sternberg tasks). Western tonal music provides naturally occurring motivic repetition and variation, recognizable units serving as WM trigger, thus allowing us to study the phenomenon of motif-tracking in the context of real music. Adopting a modern tango as stimulus, behavioural methods were used to identify the stimulus motifs and build a time-course predictor of WM neural responses. This predictor was then correlated with the participants’ functional magnetic resonance imaging (fMRI) signal obtained during a continuous listening condition. Neural correlates related to the sensory processing of a set of musical features were filtered out from the brain responses to music to aid in the exclusive recruitment of executive processes of music-related WM. Correlational analysis revealed a widely distributed network of cortical and subcortical areas, predominantly right-lateralized, responding to the WM condition, including ventral and dorsal areas in the prefrontal cortex, basal ganglia, and limbic areas. Significant subcortical processing areas, active in response to the WM condition, were pruned with the removal of the acoustic content, suggesting these music-related perceptual processing areas might aid in the encoding and retrieval of WM. The pattern of dispersed neural activity indicates WM to emerge coherently from the integration of distributed neural activity spread out over different brain subsystems (motoric-, cognitive- and sensory-related areas of the brain).